Larval rearing trials of the honeycomb grouper Epinephelus merra Bloch under laboratory conditions - Jagdis, I; Ignatius, Boby; Kandasami, D; Khan, M D Ajmal (Indian Journal of Fisheries, 2012)
Groupers being economically important food fishes are experimented widely for controlled breeding world over. In India, attempts were made on few species of the genus Epinephelus such as E. tauvina, E. malabaricus and E. polyphekadion at the Central Marine Fisheries Research Institute and limited success was achieved. The present paper discusses on larval rearing trials of the honeycomb grouper E. merra up to juvenile stage. Larvae measuring 1.3 – 1.6 mm obtained from the captive spawning of broodstock of E. merra were used for the larval rearing studies. The feeding protocol, water exchange and larval rearing methods adopted are detailed. The larval mouth opening appeared on day 3 post-hatch. The larvae gradually metamorphosed into juvenile by day 60 and attained a size of 45 mm. The possible reasons for initial mortality, the advantage of HUFA rich feeding and effect of large volume of rearing tanks on the growth and survival of the larvae are discussed.